2011
DOI: 10.1124/jpet.111.179101
|View full text |Cite
|
Sign up to set email alerts
|

1α,25-Dihydroxyvitamin D3 Up-Regulates P-Glycoprotein via the Vitamin D Receptor and Not Farnesoid X Receptor in Both fxr(−/−) and fxr(+/+) Mice and Increased Renal and Brain Efflux of Digoxin in Mice In Vivo

Abstract: Secondary farnesoid X receptor (FXR) effects, in addition to vitamin D receptor (VDR) effects, were observed in the rat liver after treatment with 1␣,25-dihydroxyvitamin D 3 [1,25(OH) 2 D 3 ], the natural ligand of VDR, caused by increased bile acid absorption as a consequence of apical sodium-dependent bile acid transporter induction. To investigate whether the increased multidrug resistance protein 1 (Mdr1)/P-glycoprotein (P-gp) expression in the rat liver and kidney was caused by the VDR and not the FXR, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
86
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 72 publications
(90 citation statements)
references
References 38 publications
2
86
2
Order By: Relevance
“…Some of these f Q values for the Q Gut model are higher than the f Q values of 0.07, 0.024, and 0.2 estimated from fits of the SFM to the data on benzoic acid (Cong et al, 2001), morphine (Cong et al, 2000), and digoxin (Liu et al, 2006), respectively, from vascularly perfused rat small intestine preparations. For digoxin, which is mainly excreted unchanged in the mouse in vivo, a value of 0.16 was found for f Q (Chow et al, 2011). The f Q terms, whether for the SFM or for Q Gut model, are less than unity Chow and Pang, 2013), with f Q values being higher (Ͼ0.3) for the Q Gut model.…”
Section: Comparison Of F Qmentioning
confidence: 92%
See 1 more Smart Citation
“…Some of these f Q values for the Q Gut model are higher than the f Q values of 0.07, 0.024, and 0.2 estimated from fits of the SFM to the data on benzoic acid (Cong et al, 2001), morphine (Cong et al, 2000), and digoxin (Liu et al, 2006), respectively, from vascularly perfused rat small intestine preparations. For digoxin, which is mainly excreted unchanged in the mouse in vivo, a value of 0.16 was found for f Q (Chow et al, 2011). The f Q terms, whether for the SFM or for Q Gut model, are less than unity Chow and Pang, 2013), with f Q values being higher (Ͼ0.3) for the Q Gut model.…”
Section: Comparison Of F Qmentioning
confidence: 92%
“…The semi-PBPK model has been used to describe midazolam inhibition by intestinal and hepatically formed metabolites, N-desmethyldiltiazem from diltiazem in humans (Zhang et al, 2009), and hydroxyitraconazole from itraconazole in rats (Quinney et al, 2008), and in the estimation of the contribution of the intestine (ϳ30 -40%) in furamidine formation from pafuramidine in a prodrug-drug relationship in rats, then humans (Yan et al, 2012). Chow et al (2011) used the combined TM-PBPK and SFM-PBPK models to predict the 1.8-and 2.6-fold induction of brain and kidney P-glycoprotein (P-gp) protein expression with the vitamin D receptor ligand, 1␣,25-dihydroxyvitamin D 3 , respectively, and demonstrated a superior fit with the SFM-PBPK model in explaining the P-gp-mediated excretion of digoxin. In the perfused rat intestine preparation in which the intestine is the only eliminating tissue, the SFM was found to be superior to the TM in describing morphine glucuronidation (Cong et al, 2000) and digoxin excretion by the P-glycoprotein under induced and noninduced states (Liu et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…CAR agonists (e.g., CITCO [6-(4-chlorophenyl)-imidazo[2,1-b][1,3] thiazole-5-carbaldehyde]) induced ABCB1 expression in brain capillary cells (Chen, 2010;Lemmen et al, 2013). VDR activation, via 1,25-dihydroxyvitamin D3, induced ABCB1 in the kidney and brain of mice (Chow et al, 2011). Chenodeoxycholic acid, a potent FXR agonist, induced ABCB1 expression in HepG2 cells (Martin et al, 2008).…”
Section: Abcb1mentioning
confidence: 99%
“…VDRresponsive transporters include the rat apical sodium-dependent bile acid transporter (Asbt) (10), human organic aniontransporting polypeptide (OATP1A2) (21), multidrug resistance protein-1 or P-glycoprotein (MDR1/P-gp) (44), and the human and rodent multidrug resistance-associated proteins (MRP2/Mrp2, Mrp3, MRP4/Mrp4) both in vitro and in vivo (14,22). Our laboratory has shown that VDR transactivates P-gp in brain microvessel endothelia (18) in vitro and P-gp in murine kidney and brain but not ileum and liver in vivo, leading to hastened efflux of digoxin in the brain and kidney (11).…”
mentioning
confidence: 99%